The Changing Global Epidemiology of Measles, 2013-2018 - Patel, Minal K; Antoni, Sebastien; Nedelec, Yoann; Sodha, Samir; Menning, Lisa; Ogbuanu, Ikechukwu U; Gacic Dobo, Marta (The Journal of infectious diseases, 2020)
Measles incidence and mortality rates have significantly decreased since vaccine introduction. Despite this progress, however, there has been a global resurgence of measles. To understand the current global epidemiology, we analyzed measles surveillance data. We analyzed data on measles cases from 2013-2018 reported to the World Health Organization. Univariate analysis was undertaken based on age, vaccination history, onset year, World Health Organization region, and World Bank income status for the country where the case was reported, and a surrogate indicator of the historical strength of the country's immunization program. Annual incidence and a 2013-2018 mean country incidence per million were calculated. From 2013 through 2018, there were 899 800 reported measles cases, of which 57% occurred unvaccinated or undervaccinated persons, with an unknown vaccination history in another 30%. Lower-middle-income countries accounted for 66% of cases, 23% occurred in persons ≥15 years of age. In countries with stronger historical vaccination programs and higher country income, case patients had higher median ages. Although most measles case patients are <15 years of age, an age shift is seen in countries with a higher income or a stronger historical vaccination program. Countries must strengthen immunization programs to achieve high vaccination coverage; some must undertake strategies to reach persons ≥15 years of age and close immunity gaps.